PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN KOPPAS SRINADI UNIT TOKO SWALAYAN RAMA - Ni Komang Tristiani; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (EMAS, 2021)
This increasingly dynamic world of work shows more and more tasks so that organizations need good Organizational Citizenship Behavior (OCB). To create OCB in employees is influenced by the attitude of their leader. Transformational leadership style, organizational culture and motivation are considered capable of stimulating the formation of OCB in the organization. The sample in this study were 65 employees of Koppas Srinadi Rama Self Service Unit. The sample research used the census method. Research data collection was carried out by observation, interviews and questionnaires. Data were analyzed using multiple linear regression analysis techniques to answer the problem formulation with the help of the Statistical Product and Service Solutions (SPSS) program. The test results show that variable 1). Transformational Leadership Style has a positive and significant effect on OCB 2). Organizational culture has a positive and significant effect on OCB 3). Work motivation has a positive and significant effect on OCB